Multilevel marketing and entrepreneurship in Thailand: a case study. Issue 1 (11th July 2016) - Hatchaleelaha, Somchai; Wongsurawat, Winai
Abstract : Purpose: The purpose of this research is to trace the development of a major player in the health / wellness direct sales industry in Thailand and draw lessons about growth strategies and approaches in dealing with common entrepreneurial challenges. Design/methodology/approach: In preparing the case study narrative, primary data from the direct experience of the company founder was combined with secondary sources of information on the landscape of direct sales industry in Thailand. Key lessons were developed from discussion and reflection on experiences of people involved in the development of the company. Findings: A multi-billion baht, direct sales business with over one hundred thousand members was built from the ground up in a span of one decade. Recruiting and retaining members with the right level of entrepreneurial drive is a constant challenge for the growing venture. Incorporating new technology to help manage information about members, customers, and stock will play a central role in creating future growth opportunities. Research limitations/implications: The research represents a single case study so generalization is naturally limited. Originality/value: Direct sales entails a considerable amount of stigma, resulting in a limited number of frank and detailed analysis of such businesses and their founding entrepreneurs. This study represents an attempt to fill this gap and will hopefully stimulate more investigation into a business model that appears to be thriving in many emerging economies in South East Asia.